HIF-1α promotes the keloid development through the activation of TGF-β/Smad and TLR4/MyD88/NF-κB pathways - Lei, Rui; Li, Jian; Liu, Feng; Li, Weihan; Zhang, Shizhen; Wang, Yang; Chu, Xi; Xu, Jinghong (Cell cycle (Georgetown, Tex.), 2019)
A keloid is defined as an overgrowth of the dense fibrous tissues that form around a wound. Since they destroy the vascular network, keloid tissues often exhibit anoxic conditions. Hypoxia-inducible factor-1α (HIF-1α) is a core factor that mediates hypoxia stress responses and regulates the hypoxic cellular and biological behaviors. In this study, we found that the expression level of HIF-1α in keloid tissue was significantly higher than that in the normal skin tissue. Hypoxia-induced HIF-1α expression significantly inhibited cellular apoptosis and promoted cellular proliferation in keloid fibroblasts but not in normal fibroblasts. Specifically, HIF-1α activated the TGF-β/Smad and TLR4/MyD88/NF-κB pathways, and the interaction of these two pathways may promote the development of keloids. Moreover, in vivo experiments showed that the inhibition of HIF-1α significantly reduced the growth of keloids.